Nematode postembryonic cell lineages - Horvitz, H R (Journal of nematology, 1982)
The complete postembryonic ceil lineages of the free-living nentatodes Caenorhabditis elegans and Panagrellus redivivus are known. Postembryonic cell divisions lead to substantial increases in the number of cells and, in most cases, in the number of types of cells in the neuronal, muscular, hypodermal, and digestive systems. The patterns of postembyronic cell divisions are essentially invariant and generate a fixed number of progeny cells of strictly specified fates. Cell fates depend upon both lineage history and cell-cell interactions: lineage limits the developmental potential of each cell and, for certain cells, cell-cell interactions specify which of a small number of alternative potential fates is acquired. Relatively simple differences in cell lineage account for some of the striking differences in gross morphology both between sexes and between species. Genetic studies indicate that these cell lineage differences reflect one or a few relatively simple mutational events. Interspecific differences in cell lineage are likely to be good indicators of evolutionary distance and may be helpful in defining taxonomic relationships. Both the techniques utilized in, and the information acquired from, studies of cell lineages in C. elegans and P. redivivus may prove useful to other hematologists